Penalaran Ilmiah dan Hasil Belajar Siswa Sekolah Dasar dalam Pembelajaran IPAS Menggunakan LKPD Multirepresentasi - Wahyuni, Vivi; Supeno, Supeno; Wahyuni, Sri (Cetta: Jurnal Ilmu Pendidikan, 2025)
The reality that emerges in the field is that not all teachers are able to implement differentiated learning that is suitable for students' ability levels, students' interests and can attract students to learn. The age of the teacher, the level of creativity, the facilities and infrastructure available at school and the support of various parties are also some of the reasons for this differentiation not happening, so that the implementation of the Merdeka Curriculum has not been fully optimized in accordance with government expectations. The non-optimal implementation of the Merdeka Curriculum is the cause of students' lack of scientific reasoning and the resulting decline in learning outcomes, especially in IPAS learning.  In connection with this problem, the purpose of this study is to examine the validity of practicality, and the effectiveness of multirepresentation-based LKPD with a scientific approach to improve scientific reasoning and learning outcomes of elementary school students in IPAS learning. This research uses a development research design (Research and Development), where the method used is research that produces products, namely in the form of multirepresentation-based LKPD with a scientific approach to force material. This research was conducted at SD Negeri Jarit 01 Candipuro District, Lumajang Regency with respondents from class IV totaling 44 students. Based on the test of the effectiveness of the product obtained N-Gain value> 70, it can be concluded that the use of multirepresentation-based LKPD using scientific approach.